Chapter 3 Mortar and Pestle or Cooking Vessel? When Archaeology Makes Progress Through Failed Analogies - Nyrup, Rune (Springer Nature, 2021)
Most optimistic accounts of analogies in archaeology focus on cases where analogies lead to accurate or well-supported interpretations of the past. This chapter offers a complementary argument: analogies can also provide a valuable form of understanding of cultural and social phenomena when they fail, in the sense of either being shown inaccurate or the evidence being insufficient to determine their accuracy. This type of situation is illustrated through a case study involving the mortarium, a characteristic type of Roman pottery, and its relation to the so-called Romanization debate in Romano-British archaeology. I develop an account of comparative understanding, based on the idea that humans have a natural desire to understand ourselves comparatively, i.e., in terms of how we resemble and differ from societies at other times and places. Pursuing analogies can provide this type of understanding regardless of whether they turn out to be accurate. Furthermore, analogies can provide a similar form of understanding even when the evidence turns out to be insufficient to determine their accuracy.